Regulated hAAT Expression from a Novel rAAV Vector and Its Application in the Prevention of Type 1 Diabetes - Ma, Hongxia (J Clin Med, 2019)
We, and others, have previously achieved high and sustained levels of transgene expression from viral vectors, such as recombinant adeno-associated virus (rAAV). However, regulatable transgene expression may be preferred in gene therapy for diseases, such as type 1 diabetes (T1D) and rheumatoid arthritis (RA), in which the timing and dosing of the therapeutic gene product play critical roles. In the present study, we generated a positive feedback regulation system for human alpha 1 antitrypsin (hAAT) expression in the rAAV vector. We performed quantitative kinetics studies in vitro and in vivo demonstrating that this vector system can mediate high levels of inducible transgene expression. Transgene induction could be tailored to occur rapidly or gradually, depending on the dose of the inducing drug, doxycycline (Dox). Conversely, after withdrawal of Dox, the silencing of transgene expression occurred slowly over the course of several weeks. Importantly, rAAV delivery of inducible hAAT significantly prevented T1D development in non-obese diabetic (NOD) mice. These results indicate that this Dox-inducible vector system may facilitate the fine-tuning of transgene expression, particularly for hAAT treatment of human autoimmune diseases, including T1D.